2023
DOI: 10.3390/molecules28052358
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity and Molecular Mechanisms of an Ursodeoxycholic Acid Methyl Ester-Dihydroartemisinin Hybrid via a Triazole Linkage in Hepatocellular Carcinoma Cells

Abstract: Hepatocellular carcinoma is the third most common cause of cancer-related death according to the International Agency for Research on Cancer. Dihydroartemisinin (DHA), an antimalarial drug, has been reported to exhibit anticancer activity but with a short half-life. We synthesized a series of bile acid–dihydroartemisinin hybrids to improve its stability and anticancer activity and demonstrated that an ursodeoxycholic–DHA (UDC-DHA) hybrid was 10-fold more potent than DHA against HepG2 hepatocellular carcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…DHA can also inhibit the activity of NADPH oxidase, thereby reducing the production of ROS (48). In addition, DHA can induce cell cycle arrest of liver cancer cells at the G 0 /G 1 phase, ROS generation and mitochondrial membrane potential loss, thereby leading to apoptosis (49). The present study demonstrated that CaMKK2-OE can significantly upregulate ATP formation and promote ROS generation in liver cancer cells, whereas knocking down NCLX expression could block these regulatory effects of CaMKK2.…”
Section: Discussionmentioning
confidence: 57%
“…DHA can also inhibit the activity of NADPH oxidase, thereby reducing the production of ROS (48). In addition, DHA can induce cell cycle arrest of liver cancer cells at the G 0 /G 1 phase, ROS generation and mitochondrial membrane potential loss, thereby leading to apoptosis (49). The present study demonstrated that CaMKK2-OE can significantly upregulate ATP formation and promote ROS generation in liver cancer cells, whereas knocking down NCLX expression could block these regulatory effects of CaMKK2.…”
Section: Discussionmentioning
confidence: 57%
“…Stability of DHA and DHA-UDCA-based hybrids in cell culture medium assessed by HPLC-MS analyses. Stability of DHA and hybrid DHA-UDC was reported in ref ; stability of hybrid DHA-t-UDCMe was reported in ref ; stability of DHA-s-UDCMe was recorded at 3, 6, 15, and 24 h. The data are presented as the mean ± SD of three independent experiments.…”
Section: Resultsmentioning
confidence: 98%
“…This compound, although not necessarily a structural analogue of DHA-t-UDCMe, has a labile ester linker between the two conjugation partners instead of the stable triazole moiety and could help elucidate the influence of the linker stability on the antiviral activity of the hybrid. The synthesis of DHA-s-UDCMe was straightforward: having obtained artesunate (ART) by following literature procedures, 45 33,34 were found stable up to 24 h of incubation in cell culture medium, whereas the parent DHA was found far more unstable, being decomposed up to 70% after 6 h (Figure 2). 33 The overall data indicated that the molecular hybridization actually improved the chemical stability with respect to the parent DHA although to a lesser extent in the case of hybrid DHA-s-UDCMe, which underwent decomposition up to 80% after 24 h.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations